Endovascular Stent Graft Placement and Coil Embolization for Splenic Artery Aneurysm with an Anatomical Variant - Kuwada, Noriaki; Akagi, Daisuke; Watanabe, Yoshiko; Kanaoka, Yuji; Tanemoto, Kazuo (International Journal of Angiology, 2022)
A 62-year-old woman with abdominal pain was diagnosed with a splenic artery aneurysm (SAA) and an anatomical variant in the splenic artery (SA) arising from the superior mesenteric artery (SMA) as its first branch. To treat the SAA, the draining artery and a small branch of the SAA were embolized, and then small-diameter stent grafts were deployed from SMA orifice, covering the aberrant origin of the SA and preserving the second branch of SMA. Intraoperative angiography confirmed successful exclusion of the SAA without endoleak or arterial dissection. The stent graft was patent and the aneurysm had shrunk 3.5 years after the operation.
Keywords: splenic artery aneurysm; splenic artery with an anatomical variant; endovascular treatment; stent graft; splenomesenteric trunk; visceral artery aneurysm; superior mesenteric artery